Age‐ and sex‐based patterns of positional behavior and substrate utilization in the golden snub‐nosed monkey (Rhinopithecus roxellana). Issue 1 (12th September 2014) - Zhu, Wen‐Wen; Garber, Paul A.; Bezanson, Michelle; Qi, Xiao‐Guang; Li, Bao‐Guo
<x xml:space="preserve">Abstract</x> Body mass plays an important role in primate positional behavior and in sexually dimorphic arboreal primate species may influence how immature and adult individuals travel through the forest canopy and access food resources. In this study, we examined age‐ and sex‐based patterns of positional behavior and substrate utilization in wild golden snub‐nosed monkeys (Rhinopithecus roxellana), an endangered species of Asian colobine. Our results indicated that among all age and sex classes, sitting was the most common feeding and resting posture and during travel, quadrupedal walking was the dominant locomotor behavior. Despite the fact that adult male R. roxellana are reported to exhibit a body mass nearly two times that of adult females, we found no significant sex differences in the positional repertoire during feeding and traveling. In addition, we found that while infants and juveniles used similar postural and locomotor behaviors as their adult counterparts, younger golden snub‐nosed monkeys more frequently engaged in risky or escape‐oriented behaviors such as climbing, running, leaping, and forelimb suspension. With increasing age, the use of quadrupedal walking and dropping (downward in‐air displacement of body mass that does not require hindlimb propulsion) increased and the use of leaping, suspensory postures, and bridging decreased. Finally, given differences in the positional repertoire of adult and immature golden snub‐nosed monkeys, we argue that studies of ontogenetic patterns of positional behavior should emphasize what it takes to survive at each life stage rather than what it takes to match an adult repertoire. Am. J. Primatol. 77:98–108, 2015. © 2014 Wiley Periodicals, Inc.